Size‐Confined Effects of Nanostructures on Fibronectin‐Induced Macrophage Inflammation on Titanium Implants. Issue 20 (1st July 2021) - Qi, Haoning; Shi, Miusi; Ni, Yueqi; Mo, Wenting; Zhang, Peng; Jiang, Shuting; Zhang, Yufeng; Deng, Xuliang
Abstract: Macrophage activation determines the fate of biomaterials implantation. Though researches have shown that fibronectin (FN) is highly involved in integrin‐induced macrophage activation on biomaterials, the mechanism of how nanosized structure affects macrophage behavior is still unknown. Here, titanium dioxide nanotube structures with different sizes are fabricated to investigate the effects of nanostructure on macrophage activation. Compared with larger sized nanotubes and smooth surface, 30 nm nanotubes exhibit considerable lesser pro‐inflammatory properties on macrophage differentiation. Confocal protein observation and molecular dynamics simulation show that FN displays conformation changes on different nanotubes in a feature of "size‐confined, " which causes the hiding of Arg‐Gly‐Asp (RGD) domain on other surfaces. The matching size of nanotube with FN allows the maximum exposure of RGD on 30 nm nanotubes, activating integrin‐mediated focal adhesion kinase (FAK)‐phosphatidylinositol‐3 kinase γ (PI3K γ) pathway to inhibit nuclear factor kappa B (NF‐ κ B) signaling. In conclusion, this study explains the mechanism of nanostructural‐biological signaling transduction in protein and molecular levels, as well as proposes a promising strategy for surface modification to regulate immune responses on bioimplants. Abstract : The matching size of nanotubes with fibronectin allows the maximum exposure of Arg‐Gly‐Asp on 30 nm nanotubes, activating integrin‐mediated FAK‐PI3K γ pathway to inhibit NF‐ κ B signaling. The reduction of the NF‐ κ B eventually results in 30 nm titanium nanotubes exhibiting better biocompatibility with less macrophage activation, compared with 80 nm nanotubes and plane TiO2 .